Pemberdayaan Karang Taruna Dusun Gaplek dalam Pemanfaatan imbah Kotoran Sapi dan Kulit Kopi sebagai Bahan Non-Addhesive Bio-briquettees Berbasis Green Economy - Dana Raja, Kusuma; Akbar Rizqi Maulana, Alfian; Alfi Fredyansyah, Maulana; Poma, Yoniva Nandarista Poma; Entikaria Rachmanita, Risse (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
This research aims to develop non-adhesive biobriquettes made from coffee husk waste and cow dung as the main raw materials. This initiative is expected to be a sustainable solution in organic waste management and provide economic benefits to the community. The method used includes the process of mixing, molding, and drying the raw materials without using additional adhesives. The results show that the biobriquettes produced have a high calorific value and can compete with conventional biobriquettes that use chemical adhesives. In addition, the application of this technology in the community has a positive impact in the form of increased awareness of the importance of waste management and local economic development through the production of biobriquettes. Thus, this study concludes that non-adhesive biobriquettes from coffee husk waste and cow dung have great potential to be further developed as an alternative energy source that is environmentally friendly and empowers the community. Keywords — Non-adhesive biobriquettes, Coffee husk waste, Cow dung